THE USE OF TRI-GEOPHYSICAL METHODS FOR CONCEALED KARST CAVITIES LOCATION NEAR HAQLANYIAH TOWN - Abdul Razzak, Mohammad; Zaynal, Mohammad (Iraqi Journal of Science, 2024)
The main objective of the present work is to find, locate and delineate somesubsurface morphological structures at area near Haqlanyiah town lying in thewestern part of Iraq, either as an isolated karst cavity features or as buried channelfeatures by using three different geophysical methods, representing byelectromagnetic conducting method, VLF-Radiohm electromagnetic resistivitymethod and electrical resistivity method with horizontal profiling using wennerarray. The study area accupies an area (100x300m) and the survey was carried outalong thirty one traverses with (10m) separation and (10m) grid interval. Theelaborated field data were subjected to the process of analysis, a great coincidencebetween method results is obtained, then the results show a presence of twoanomalous zones in which its characteristic features gave an indication of a presencetwo possible elongated concealed channels trending in two different directions as inE-W and NW-SE